Anterior Cervical Discectomy with Fusion in Patients with Degenerative Cervical Disc Disease - Hadi Hameed , Himdad; Khaleel Hammood, Emad (Diyala Journal of Medicine, 2020)
Background: Anterior cervical discectomy with fusion (ACDF) is challenging with respect to both patient selection and choice of surgical procedure. Objective: To determine the age of patients with degenerative cervical disc disease undergoing surgery, to determine the clinical and radiological findings of degenerative cervical disc disease, and to find out the rate of success for relieving pain and radiculopathy. Patients and Methods: This is a clinical prospective study of 50 patients (case series of patients with chronic degenerative cervical disease) operated on from October 2015 to October 2018. Their ages ranged from 48-78 years, they were treated with anterior cervical discectomy with fusion, and fusion was achieved with Polyether ether ketene (PEEK) cage. Follow up using visual analog scale (VAS), out of 10 scores, was done for at least one year after the operation (at six months, nine months and one year postoperatively) for both neck pain and shoulder pain (radicular pain). Results: The mean age + SD was 63.8 + 8.4 years, 54% of the patients were females, 92% of the patients had single level ACDF, and 8% had multiple levels ACDF. The most common presentation in both genders was pain & radiculopathy (56%), followed by radiculopathy (28%), and less common presentation was pain alone (16%). The patient who has short history of the symptom (less than 6 months) gave good postoperative results and showed improvement in the symptom, 64% of the patients improved and 4% of them had no change.In the 2nd group (the symptom more than 6 months): 10 patients improved out of 16 (62.5%), four of them had no change and two of them deteriorated & re-operated for adjacent level. Conclusion: ACDF is an effective treatment for pain & radiculopathy in selected patients with chronic degenerative cervical disease (CDCD) after one year of follow up.